"What's my risk of sustaining an ACL injury while playing sports?" A systematic review with meta-analysis. Issue 16 (7th August 2019) - Montalvo, Alicia M; Schneider, Daniel K; Yut, Laura; Webster, Kate E; Beynnon, Bruce; Kocher, Mininder S; Myer, Gregory D
Abstract : Objective: To estimate the incidence proportion (IP) and incidence rate (IR) for ACL injury in athletes. Design: Systematic review with meta-analysis Data sources: The PubMed, CINAHL and SPORTDiscus electronic databases were searched from inception to 20 January 2017. Eligibility criteria for selecting studies: Studies were included if they reported total number of participants/population by sex, total number of ACL injuries by sex and total person-time by sex. Results: Fifty-eight studies were included. The IP and IR of ACL injury in female athletes were 3.5% (1 out of every 29 athletes) and 1.5/10 000 athlete-exposures over a period of 1 season-25 years. The IP and IR of ACL injury in male athletes were 2.0% (1 out of every 50 athletes) and 0.9/10 000 athlete-exposures over a period of 1–25 years. Female athletes had a higher relative risk (RR) for ACL injury compared with males (RR=1.5; 95% CI 1.2 to 1.9; P<0.01) and a higher incidence rate ratio (IRR) of ACL injury compared with males over 1 season–25 years (IRR=1.7; 95% CI 1.4 to 2.2; P<0.010). When accounting for participation level, the disparity in the IR between female and male athletes was highest for amateur athletes compared with intermediate and elite athletes (IRR=2.1; 95% CI 1.3 to 3.4; P<0.01; I²=82%). Amateur female athletes remained at higher risk of ACL injury than did with amateur male athletes. In studies where follow-up length was <1 year, female athletes had a higher IR of ACL injury than did to males (IRR=1.7; 95% CI 1.3 to 2.2; P<0.01). Where follow-up was 1 year and beyond, there was no sex difference in the IR of ACL injury (IRR=2.1; 95% CI 0.9 to 4.8; P=0.06; I²=65%). Summary/conclusions: One in 29 female athletes and 1 in 50 male athletes ruptured their ACL in a window that spanned from 1season to 25 years. The IR of ACL injury among female athletes in a season was 1.7 times higher than the IR of ACL injury among male athletes and the IP of ACL injury among female athletes was 1.5 times higher than the IP of ACL injury among male athletes. The reported sex disparity in ACL injury rates is independent of participation level and length of follow-up.